INSTALLATION FOR DETERMINATION OF HEAT RELEASE OF HEATING RADIATORS: Array - Ivashina, Yu.; Zavodyannyi, V. (Municipal economy of cities. Series: «Economy science», 2021)
To calculate the share of thermal energy consumed by this apartment in an apartment building, it is necessary to determine the heat transfer of all heating radiators in the house. But the heat transfer given in the passport of the heating device corresponds to the temperature pressure equal to 70K. Often the owners install non-standard devices, so the problem of determining the heat transfer of heating radiators in real conditions is relevant. Thermometric method, which is called electric, is widely used for laboratory determination of heat transfer of heating devices. Water by means of the pump circulates through an electric copper and the investigated radiator. The heat output of the latter is defined as the difference between the supplied electrical power (boiler power plus pump) and heat loss. The purpose of the work is to develop and study the operation of the installation for determining the heat transfer of heating radiators, which had a simpler design and could ensure proper measurement accuracy. We have proposed a scheme and design of the installation for determining the heat transfer of electric heating radiators, which differs in that it does not include a circulating pump. Water in the system circulates under the action of gravity due to changes in the density of the coolant during heating and cooling. This greatly simplifies the circuit by eliminating not only the pump but also the valve and the air outlet valve. The heater chamber is made of a steel pipe with a diameter of 88 mm. A steel cover is attached to the lower flange, through which a 1-1.5 kW heater is introduced into the chamber. Two 1/2 ″ sections of pipe are welded to the body of the heater chamber, through which the radiator is connected by means of rubber couplings. The cylindrical surface of the chamber on top of the layer of internal insulation is covered with a shielding heater, the temperature of which is maintained equal to the surface temperature of the heater chamber in the middle part. A layer of external thermal insulation is installed on top of the shielding heater. To determine heat loss, the radiator is disconnected from the heater chamber, plugs are installed and insulated. In stationary mode, the dependence of the heater power on the temperature of the heater chamber is measured, which determines the power of heat losses. The simplification of the installation has led not only to its reduction in price, but also to an increase in accuracy due to the reduction of heat losses and the simplicity of their definition.